Correlation study of serum vitamin D, total IgE and eosinophils in children with atopic dermatitis - Jinling FU; Qilin LI; Chun PANG (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2021)
Objective Serum levels of vitamin D (VitD), total immunoglobulin E (tIgE) and eosinophil ratio (EOS%) in children with atopic dermatitis (AD) were measured in order to determine the relationship between VitD and AD, and its immunoregulatory role in AD. Methods Serum samples were collected from 120 patients with AD and 60 healthy controls. Enzyme-linked immunosorbent assay (ELISA) was performed to detect the serum levels of 25(OH)D in the AD and controls, and the total serum IgE levels in the AD group. Blood cell analyzer was used to determine the proportion of blood eosinophils in the AD group. Results The serum level of 25(OH)D was significantly lower in the AD group (62.99±17.38) nmol/L than that in the healthy controls (72.44±18.07) nmol/L(t=2.92, P<0.01). The mean value of 25(OH)D did not differ significantly among slight AD, moderate AD and severe AD groups (F=1.32, P=0.275). In the AD patients, serum levels of VitD was negatively correlated with total serum IgE level (r=-0.38, P=0.003), but no correlation was found between the serum level of 25(OH)D and the proportion of blood eosinophils (r=-0.03, P=0.827). Conclusion The level of 25(OH)D in children with AD is low, and negatively correlated with tIgE levels, with no correlation with EOS ratio.